2012
DOI: 10.1007/s00214-012-1154-6
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of molecular excited states in polar organic monolayers via an efficient embedding approach

Abstract: In this work, we present a theoretical investigation on excitation energies of organic molecules embedded in a periodic monolayer. We use the self-consistent periodic-image-charges embedding approach, which takes into account all the electrostatic effects, to compute the perturbation on molecular orbitals and eigenvalues due to the presence of the surrounding periodic array of polar molecules. We considered vanadyl naphthalocyanine, mercaptobiphenyl, and tris-(8-hydroxyquinoline) aluminum (AlQ 3 ) at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Such an approach can be realized using various quantum mechanics/molecular mechanics (QM/MM) schemes (Bjornsson & Bü hl, 2012). It has been recently shown that constrained QM/MM geometry optimizations of excited state species provide almost quantitative agreement with the experimental results (Benedict et al, 2011;Makal et al, 2012Makal et al, , 2011Terentjevs et al, 2012). Moreover, this method is computationally cheap and robust.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach can be realized using various quantum mechanics/molecular mechanics (QM/MM) schemes (Bjornsson & Bü hl, 2012). It has been recently shown that constrained QM/MM geometry optimizations of excited state species provide almost quantitative agreement with the experimental results (Benedict et al, 2011;Makal et al, 2012Makal et al, , 2011Terentjevs et al, 2012). Moreover, this method is computationally cheap and robust.…”
Section: Introductionmentioning
confidence: 99%